ANALISA FAKTOR YANG MEMPENGARUHI RESIKO JATUH PADA LANSIA DENGAN DIABETES MELITUS TIPE 2 DI KOTA MALANG - Paramitha, Pradnya Asih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Type 2 diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels, decreased insulin secretion by pancreatic beta cells or impaired insulin action (insulin resistance). Type 2 diabetes mellitus is a health problem that often occurs in the elderly and can increase the risk of falling, causing injury and causing sudden death in the elderly. The risk of falling is an event reported by a patient or family who saw or heard of an incident that resulted in a person suddenly lying down, sitting on the floor or in a lowered position, with pr without loss of consciousness or injury.